THE ROLE OF MOLECULAR DIAGNOSTICS (PCR) IN CLINICAL LABORATORY PRACTICE - Rajabboyev Shoxruz; Nurmatova M.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Molecular diagnostics has become an essential component of modern clinical laboratory practice. Among various molecular techniques, the Polymerase Chain Reaction (PCR) is one of the most widely used methods for the detection and analysis of genetic material. PCR allows rapid and accurate identification of infectious agents, genetic mutations, and oncological markers. Its high sensitivity and specificity make it a powerful tool for early diagnosis, disease monitoring, and treatment selection. This article discusses the principles of PCR, its types, clinical applications, and its importance in contemporary laboratory medicine.[1]